Genomic DNA isolation from dried blood using gelatin-coated magnetic particles - Sorasak Intorasoot (2018)
Gelatin-coated magnetic particles were implemented for isolation of human genomic DNA from dried blood spotted onto glass microfibre filters. The DNA quality and quantity were compared to a silica-based membrane purification kit. Conditions for dried blood storage were varied for DNA stability determination. Approximately three times higher DNA yield was recovered by coated magnetic particles than the silicabased kit. In addition, the quality of extracted DNA was determined using β-actin gene amplification by polymerase chain reaction (PCR). It was implied that genomic DNA was stable for at least 28 days in a dried condition. Gelatin-coated magnetic particles are rapid, simple and useful for DNA extraction in field applications.